2021
DOI: 10.1002/1878-0261.12956
|View full text |Cite
|
Sign up to set email alerts
|

ST6GalNAc‐I promotes lung cancer metastasis by altering MUC5AC sialylation

Abstract: mutant p53 R175H mediates ST6GalNAc-I expression, leading to the sialyation of MUC5AC, and thus contribute to LC liver metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 50 publications
(91 reference statements)
1
15
0
Order By: Relevance
“…However, a significant increase of hSTGalNAc I gene expression by curcumin was not observed in A549, U-87 MG and MCF-7 cells, indicating a cell typespecific hSTGalNAc I gene expression by curcumin. Similarly, previous studies showed that most breast cancer cell lines, such as MCF-7, MDA-MB-231 and T47D (Julien et al, 2001(Julien et al, , 2006Sewell et al, 2006), and lung cancer cell line, including A549 (Lakshmanan et al, 2021), do not express hST6GalNAc I mRNA transcript or sTn antigen.…”
Section: Discussionsupporting
confidence: 60%
“…However, a significant increase of hSTGalNAc I gene expression by curcumin was not observed in A549, U-87 MG and MCF-7 cells, indicating a cell typespecific hSTGalNAc I gene expression by curcumin. Similarly, previous studies showed that most breast cancer cell lines, such as MCF-7, MDA-MB-231 and T47D (Julien et al, 2001(Julien et al, , 2006Sewell et al, 2006), and lung cancer cell line, including A549 (Lakshmanan et al, 2021), do not express hST6GalNAc I mRNA transcript or sTn antigen.…”
Section: Discussionsupporting
confidence: 60%
“…Dysregulated MUC5AC expression and its oncogenic role have been documented in malignant conditions, including colon, pancreatic and lung cancers. [20][21][22] It has been shown that during the progression from atypical lung adenomatous hyperplasia to adenocarcinoma, MUC5AC expression gradually increases, suggesting that MUC5AC may promote the development of lung adenocarcinoma. 17 In the present study, higher MUC5AC expression was found in lung ADC tissue than in adjacent normal lung tissue and correlated with worse disease-free survival and overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulated MUC5AC expression and its oncogenic role have been documented in malignant conditions, including colon, pancreatic and lung cancers 20–22 . It has been shown that during the progression from atypical lung adenomatous hyperplasia to adenocarcinoma, MUC5AC expression gradually increases, suggesting that MUC5AC may promote the development of lung adenocarcinoma 17 .…”
Section: Discussionmentioning
confidence: 99%
“…ST6GalNAc‐I is an O‐glycosyltransferase that catalyzes the addition of sialic acid to the initiating GalNAc residues forming sialyl Tn (STn) on glycoproteins. In lung cancer, Lakshmanan et al 10 . demonstrated that mutant p53 R175H mediates ST6GalNAc‐I expression, leading to the sialyation of MUC5AC.…”
Section: Figurementioning
confidence: 99%
“…9 ST6GalNAc-I is an O-glycosyltransferase that catalyzes the addition of sialic acid to the initiating GalNAc residues forming sialyl Tn (STn) on glycoproteins. In lung cancer, Lakshmanan et al 10 demonstrated that mutant p53 R175H mediates ST6GalNAc-I expression, leading to the sialyation of MUC5AC. GALNT3, GALNT5 and B3GNT3 GTs mRNA expression were downregulated in ST6GalNAc-I KO cells, whereas FUT9, COLGALT2, HAS3 and ST8Sia2 were upregulated in lung cancer cells.…”
mentioning
confidence: 99%